2021
DOI: 10.1038/s41598-021-89261-w
|View full text |Cite
|
Sign up to set email alerts
|

Publisher Correction: The impact of smoking different tobacco types on the subgingival microbiome and periodontal health: a pilot study

Abstract: An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Tobacco smoking disturbs the oral microbiome via immunosuppression, oxygen deficiency, antibiotic effects, and other likely mechanisms 3 . The subgingival and supra gingival microbiota composition in smokers of various tobacco products including medwakh, shisha, and cigarette was reported in our previous studies 4 , 5 . It has been reported that the microbiome of these types of tobacco smokers was altered in both supra and subgingiva, making them more susceptible to severe periodontal disorders 4 and dental caries 6 .…”
Section: Introductionmentioning
confidence: 53%
“…Tobacco smoking disturbs the oral microbiome via immunosuppression, oxygen deficiency, antibiotic effects, and other likely mechanisms 3 . The subgingival and supra gingival microbiota composition in smokers of various tobacco products including medwakh, shisha, and cigarette was reported in our previous studies 4 , 5 . It has been reported that the microbiome of these types of tobacco smokers was altered in both supra and subgingiva, making them more susceptible to severe periodontal disorders 4 and dental caries 6 .…”
Section: Introductionmentioning
confidence: 53%